Vibrations - Balachandran, Balakumar; Magrab, Edward B. 1938- (Cambridge mathematical textbooks, 2019)
"Vibrations: This new edition explains how vibrations can be used in a broad spectrum of applications and how to meet the challenges faced by engineers and system designers. The text integrates linear and nonlinear systems and covers the time domain and the frequency domain, responses to harmonic and transient excitations, and discrete and continuous system models. It focuses on modeling, analysis, prediction, and measurement to provide a complete understanding of the underlying physical vibratory phenomena and their relevance for engineering design"...